Increased clearance of plasma cholesterol after injection of apolipoprotein E into Watanabe heritable hyperlipidemic rabbits. - Yamada, N (1989)
Apolipoprotein E (apoE) is known to play an important role in lipoprotein metabolism. We have studied the effect of apoE on the metabolism of plasma cholesterol by injecting apoE intravenously into rabbits deficient in low density lipoprotein receptors [Watanabe heritable hyperlipidemic (WHHL) rabbits]. Approximately 30 mg of apoE was injected per rabbit; a total of five WHHL rabbits were used. One hour later, plasma cholesterol levels fell 8.3% (from 488 +/- 192 to 446 +/- 174 mg/dl). After 3 hr, cholesterol levels had fallen by 19% (to 392 +/- 152 mg/dl). The reduced levels were maintained for at least 8 hr after injection of apoE. Cholesterol in very low density lipoproteins (VLDLs) and intermediate density lipoproteins fell rapidly during the first 2 hr after injection, followed by a reduction in the low density lipoprotein cholesterol level. Changes in apolipoprotein B levels in each lipoprotein fraction were very similar to those of cholesterol. Plasma apoE levels 3 min after injection were elevated 3-fold to 22.8 +/- 6.3 mg/dl and returned to initial levels 8 hr after injection. The rate of removal of intravenously injected 125I-labeled VLDL that had been incubated with apoE was 3-fold higher than that of unmodified VLDL. From these results, we conclude that the injected apoE is incorporated into VLDLs and that VLDL particles carrying more apoE are removed from the blood more rapidly, resulting in reduced formation of low density lipoprotein and lowered cholesterol levels.